Criteria for evaluation of knowledge in the process of studying the discipline «Organization and methods of improving physical culture» - Марченко, С. І. (Physical Education Theory and Methodology, 2014)
The purpose of research — justify the assessment criteria of student learning in the study course «Organisation and Methods of Physical Culture» for educational qualification of 6.01020101 — Bachelor. Methods of research — theoretical analysis and synthesis of the literature data, systematic approach. The main results of the study. The concept of assessment of the course «Organization and methods of improving physical training» is systematic presentation of the material, which allows to form students’ knowledge, skills and practical skills required physical education teachers to organize and conduct various forms of fitness training.